APPLICATION OF MIND MAPPING TO INCREASE IPS MATERIAL CONTROL AT SMPN 7 PALANGKA RAYA - Silvia Arianti (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
The purpose of this study was to determine how the application of Mind Mapping methods to increase student participation and student mastery of the IPS material in class VIII SMPN 7 Palangkaraya. This study is a class action (Classroom Action Research), the method Kemmis and Taggart are conducted in two cycles, valuation done each cycle end to determine whether there is an increase in the participation of students in IPS and student mastery of the IPS material. Action is given in the form of application of the model Mind Mapping as an effort to improve the IPS learning and increase student participation and mastery of the IPS material. The results showed that the method of Mind Mapping learning, success to increase the participation of student learning and mastery of the IPS material. This is evidenced by the increasing activity of students. Students have the courage to ask, answer the questions, discuss and cooperate with other members of the group to make Mind Mapping, mastery increasing of the IPS material can be seen from the acquisition value of the students before the action given, ie an average of 60, to 65 in the first cycle mastery performance of the material before action up to as many as 16 students (66.65%) increased to 17 students (70.83%). In the second cycle the average value increased to 70 and students who have achieved mastery of as many as 20 students (83.33%) at the end of the test cycle the average value of students into 77.50, students who have achieved mastery of as many as 21 students (87, 50%), Mind Mapping method in variation with other methods capable of increasing mastery of the IPS material in class VIII SMPN 7 Palangkaraya, because Mind Mapping learning method can create an atmosphere of active learning, creative, and fun.